Напрямки підвищення ефективності управління фінансовою стійкістю на підприємстві - Геращенко, Ірина Олексіївна (НТУ "ХПІ", 2018)
Визначено поняття фінансової стійкості підприємства. Визначено тактичні та оперативні цілі з метою відновлення, покращення та стабілізації фінансового стану підприємства. Виявлено причини , які впливають на фінансову стійкість підприємства. Розроблено та систематизовано шляхи підвищення ефективності управління фінансовою стійкістю на підприємстві. Розроблено етапи комплексного фінансового планування забезпечення фінансової стійкості підприємства. Зроблено висновки про необхідність проведення аналізу показників фінансової стійкості, знаходження причин, які стали на заваді більш стабільного фінансового положення підприємства та знаходження шляхів щодо покращення фінансової стійкості підприємства.

The concept of financial stability of the enterprise is defined. The greatest attention in the system of measures aimed at financial stabilization in the context of a crisis situation should be given to the recovery phase and strengthening the level. Financial sustainability of the enterprise - the key to eliminating insolvency and financial strategy aimed at improving the financial condition of the company and economic growth in the prospective period. Tactical and operational goals have been defined with the purpose of restoration, improvement and stabilization of the financial condition of the enterprise. The reasons that influence the financial stability of the enterprise are revealed. Decisive factor in building the goals of the enterprise is efforts to ensure the profitability of the enterprise and the maintenance of the stability of financial indicators. Such a variety of reasons influencing the activities of a market enterprise leads to various aspects of its stability, including general, price, financial, and depending on the factors affecting it, internal and external aspects. The ways of improving the efficiency of financial sustainability management at an enterprise are developed and systematized. The stages of complex financial planning for ensuring financial stability of the enterprise are developed. The conclusion is made on the need to analyze the indicators of financial sustainability, finding the reasons that have prevented a more stable financial position of the company and finding ways to improve the financial sustainability of the enterprise. The priority directions of increasing the efficiency of management of financial stability of enterprises in Ukraine are determined.
Directions to improve efficiency of financial stability management at the enterprise
Keywords: фінансова стійкість; показники фінансової стійкості; оперативні цілі; тактичні цілі; фінансовий план; платоспроможність; ефективне управління; фінансова стратегія; financial sustainability; financial sustainability indicators; tactical goals; financial plan; solvency; effective management; financial strategy; operational goals